Perovskite La0.3Sr0.7Fe0.7Cr0.3O3−δ Catalysis Raises the Bar: Preventing Unwanted Near‐Surface Sr Segregation and SrCO3 Precipitation. Issue 1 (7th August 2021) - Fidelsky Kozokaro, Vicky; Caspary Toroker, Maytal
Abstract: Sr surface segregation (SSS) in perovskite materials is a main factor causing efficiency degradation of solid oxide fuel cells (SOFC's), and therefore can affect the La0.3 Sr0.7 Fe0.7 Cr0.3 O3− δ perovskite, which is known as a compatible anode and cathode in a reversible and symmetric SOFC. As a result of segregation, the atomic rearrangements in the near‐surface environment are likely to generate additional phases to the original one such as strontium carbonate (SrCO3 ) at high CO2 pressure. In the current work, first principal calculations are carried out for modeling the initial formation of SrCO3 after Sr segregation in LSFCr with CO2 presence. It is found that the tendency of CO2 to participate in SrCO3 phase formation is a competing reaction to its reduction to CO on the LSFCr material, and O vacancies are needed not only to improve CO2 reduction but also to block the competing reaction of SrCO3 adsorption. Therefore, LSFCr successfully "raises the bar" of CO2 reduction catalytic efficiency by preventing unwanted Sr segregation at high concentrations of surface oxygen vacancies. Abstract : Sr surface segregation in perovskite materials is a main factor causing efficiency degradation of solid oxide fuel cells, resulting in atomic rearrangements in the near‐surface environment and generation of additional phases to the original perovskite. In the current work, first principle calculations are carried out for modeling the initial formation of SrCO3 after Sr segregation in LSFCr (La0.3 Sr0.7 Fe0.7 Cr0.3 O3− δ ) with CO2 presence.